2002
DOI: 10.1002/1521-3862(20020304)8:2<74::aid-cvde74>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature MOCVDof Conducting, Micrometer-Thick, Silver Films

Abstract: Silver layers up to 3 lm thick have been deposited at 250±510 C using a simple powder flash evaporation MOCVD procedure with a silver pivalate as the volatile precursor. Carbon-free deposits could be obtained at temperatures ³ 310 C. A very high deposition rate of 10 lm h ±1 has been achieved. The silver layers were dense and conducting. Properties of silver pivalate, and the influence of deposition temperature on film microstructure, are discussed. The procedure is a cheap and robust route to silver coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[109] Various silver metal-organic compounds have been used in AACVD as precursors for silver and silver-alloy films, such as silver carboxylates, fluoro-X. [109] Various silver metal-organic compounds have been used in AACVD as precursors for silver and silver-alloy films, such as silver carboxylates, fluoro-X.…”
Section: Metallic Filmsmentioning
confidence: 99%
“…[109] Various silver metal-organic compounds have been used in AACVD as precursors for silver and silver-alloy films, such as silver carboxylates, fluoro-X. [109] Various silver metal-organic compounds have been used in AACVD as precursors for silver and silver-alloy films, such as silver carboxylates, fluoro-X.…”
Section: Metallic Filmsmentioning
confidence: 99%
“…These are summarized in Figure 7, with the same carried out for a film deposited using 5% H 2 /N 2 for comparison. Previous work 8,44 found that Ag deposition with a small quantity of H 2 assisted in the reduction of halide contamination due to the formation of hydrogen halides, though there was no trace of F in any films deposited here, regardless of carrier gas. In the case of deposition from silver trifluoroacetate, hydrogen fluoride was reported form preferentially over C x H y such that solid C is codeposited with Ag.…”
Section: Blanks Appear In Tablementioning
confidence: 61%
“…12 It is generally expedient for industrially scalable deposition processes to minimize cost by avoiding vacuum deposition methods such as MOCVD and MS; however, atmospheric-pressure thermal CVD (APCVD) of silver films is virtually unheard of due to a lack of available precursors with suitably high vapor pressures. 8 High-performance silver thin films have been deposited at atmospheric pressure using flameassisted CVD (FACVD); 13 however, this technique is typically limited to small-scale sample preparation due to significant temperature variations, and therefore nonuniformity in the deposited films, being intrinsic to the method. 14 Aerosol-assisted chemical vapor deposition (AACVD) is an atmospheric-pressure alternative to thermal APCVD, which avoids the requirement of thermal APCVD that precursors should be appreciably volatile by instead generating an aerosol from a solution of the precursor.…”
Section: Introductionmentioning
confidence: 99%
“…[109][110][111] However, also in wet chemical coating techniques silver carboxylates could be used. Compared to inks based on nanoparticle suspensions they do not contain any solids tending to agglomeration.…”
Section: Metal Organic Precursorsmentioning
confidence: 99%
“…Silver diketonates and silver carboxylates have been developed initially as precursors for CVD processes. [109][110][111] However, also in wet chemical coating techniques silver carboxylates could be used. Since most of these structures are insoluble due to their polymeric or oligomeric structures, Lewis bases such as phosphane, phosphite, bipyrimidine are often added as co-ligands.…”
Section: Nanoparticle Dispersionsmentioning
confidence: 99%